Harmonic rhythm : analysis and interpretation - Swain, Joseph Peter (OUP E-Books., 2002)
An accessible exploration of an important and understudied music theory topic, Swain's book examines the dimensional technique of analyzing harmonic rhythm. Simply defined, harmonic rhythm is the relationship between changes in harmony and perceived changes in rhythm. This phenomenon plays a large role in shaping the texture and style of much of Western music, from Renaissance polyphonic pieces to the works of Debussy. Swain provides a clear and thorough discussion of how harmonic theory works, using a small core of repeated musical examples.